PERANAN BRAND ANTHROPOMORPHISM DALAM MEMBENTUK KECINTAAN MEREK DAN LOYALITAS MEREK (STUDY PADA KONSUMEN MOBIL EROPA DI INDONESIA) - Pramatatya Resindra Widya; Adi Mursalin (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The aim of this study is to examine the influence of brand anthropomorphism on brand love and its impact on brand loyalty. The study used a quantitative approach with survey methods. The sample in this study amounted to 250 European car users spread across Jakarta, Yogyakarta, Central Java, East Java.The analysis Model in this study will be divided into 3 stages of analysis. The first stage of multiple regression analysis, the second stage of simple regression analysis. The third stage of the moderation test with hierarchical moderated regression Brand anthropomorphism has a positive effect on the formation of brand love. Brand love has a positive effect on brand engagement. For further research it is recommended to add subjective norm variables to this research model.